Recent Trends in Islamic Revivalism in Malaysia - M. Syukri Salleh (Studia Islamika, 1999)
The focus of the article is on the trends of Islamic revivalism before the sacking of Anwar, though where necessary, the Anwar issue has been mentioned briefly for reference. Specifically, this paper attempts, firstly, to understand the trend of Islamic revivalism before the Anwar Ibrahim episode; secondly, to analyze the factors and reasons that culminated in the changing of approach from confrontational to non-confrontational; and thirdly, to seek answers to several vital questions relating to the form of Islamic revivalism in the country that has been molded by this developing trend. Since these findings are based on on-going researchs the arguments embodied in this paper should be considered rather preliminary.DOI: 10.15408/sdi.v6i2.730